Fecal Microbiota Transfer to Determine the Contribution of the Gut Microbiome in a Mouse Model of Western Diet-Enhanced Colorectal Cancer. (14th June 2022) - Rodriguez, Daphne; Benninghoff, Abby; Hintze, Korry; Rompato, Giovanni; Stewart, Eliza
Abstract: Objectives: The role of the gut microbiome in the etiology of colorectal cancer (CRC) and the therapeutic potential for modulation of gut microbiota is under intense investigation. Previously, we showed that consumption of the total Western diet (TWD) in mice increased gut inflammation, promoted colon tumorigenesis, and altered the microbiome composition compared to mice fed a healthy diet, AIN93G (AIN). However, it is unclear whether the gut microbiome contributes directly to colitis-associated CRC in this model. The objective of this study was to determine whether fecal microbiota transfer (FMT) from host mice fed either AIN or TWD basal diets would alter colitis symptoms or colitis-associated CRC in recipient mice, which were fed either AIN or TWD directly. Methods: The resident microbiome of recipient mice was depleted using broad spectrum antibiotics and then replenished by FMT using fecal samples collected during a prior experiment from mice fed either AIN diet (resulting in modest colitis and low tumor burden) or TWD diet (extreme colitis and high tumor burden) in a time-matched fashion by week. Recipient mice were fed either AIN or TWD basal diets, such that four experiment groups were generated: 1) AIN-fed recipients with FMT from AIN-fed host, 2) AIN-fed recipients with FMT from TWD-fed host, 3) TWD-fed recipients with FMT from AIN-fed host, 2) TWD-fed recipients with FMT from TWD-fed host. In recipients, the standard azoxymethane + dextran sodium sulfate model of colitis-associated CRC was used. Results: Preliminary results indicate that time-matched FMT from mice fed TWD did not significantly enhance symptoms of colitis, colon epithelial inflammation, mucosal injury, or colon tumor burden in recipient mice fed AIN diet. Conversely, FMT from AIN-fed mice did not impart a protective effect for recipient mice fed the TWD. Conclusions: FMT from mice fed either basal diet with differing colitis or tumor outcomes did not shift colitis symptoms of colon tumorigenesis in recipient mice, regardless of the basal diet they consumed. These observations suggest that the gut microbiome may not contribute directly to the development of disease in this animal model. Gut microbiome 16s rRNA sequencing and analyses are pending. Funding Sources: Funding support USDA NIFA grant no. 2018–67, 017-27, 516.